2002
DOI: 10.1021/jm010323l
|View full text |Cite
|
Sign up to set email alerts
|

Common and Selective Molecular Determinants Involved in Metabotopic Glutamate Receptor Agonist Activity

Abstract: Several potent and group selective agonists of metabotropic glutamate receptors (mGluRs) have been docked at mGlu1,2,4R binding sites in the closed conformation of the bilobate extracellular domain. Quisqualic acid and (S)-3,5-dihydroxyphenylglycine (3,5-DHPG) were selected for mGlu1R, dicarboxycyclopropylglycine (DCG-IV), LY354740, (S)-4-carboxyphenylglycine (4CPG) for mGlu2R, and (S)-2-amino-4-phosphonobutyric acid (AP4), 1-aminocyclopentane-1,3,4-tricarboxylic acid (ACPT-I), (S)-4-phosphonophenylglycine (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 58 publications
3
93
0
Order By: Relevance
“…The extensive nature of interlobe connections in mGluRs was also noted previously (15). Direct interlobe interactions found in the closed conformation of mGluRs manifest as both electrostatic and hydrophobic interactions in the model of T1R2.…”
Section: Resultssupporting
confidence: 75%
“…The extensive nature of interlobe connections in mGluRs was also noted previously (15). Direct interlobe interactions found in the closed conformation of mGluRs manifest as both electrostatic and hydrophobic interactions in the model of T1R2.…”
Section: Resultssupporting
confidence: 75%
“…This site is conserved in all mGluRs, except in mGlu2 where site 2 is occupied by the negatively charged carboxylate moiety of Asp146, which likely mimics Cl 2 . This carboxylate moiety makes hydrogen bonds with the NH backbone of Tyr216 and a salt bridge with Arg271, a residue involved in interlobe connections through a cation-p interaction with Tyr144 and a salt bridge with Glu273 (64), as confirmed in a recent crystal structure of mGlu2 (65). Interestingly, mGlu2 is also the least-sensitive mGluR to Cl 2 .…”
Section: Discussionmentioning
confidence: 76%
“…In the case of MAP4, the ␣-methyl group makes steric bumps with the aromatic ring of Tyr-227, whereas the third carboxylic group of ACPT-II, lying close to the carboxylic group of Asp-309, causes ionic repulsion. In contrast, when the same approach was used to dock the mGlu8 potent agonist ACPT-I, a stereoisomer of ACPT-II, the third COO Ϫ group was oriented differently at the binding site and can be accommodated well in a closed form of the binding pocket (6,20,34).…”
Section: Resultsmentioning
confidence: 99%
“…These studies revealed two major conformational changes resulting from agonist binding. A first one is the closure of at least one VFTM in the dimer, as expected from modeling studies of other family 3 GPCRs (6,(8)(9)(10)20). Indeed, glutamate binds to lobe I within the cleft that separates both lobes and also can interact with residues from lobe II leading to the stabilization of a closed state.…”
mentioning
confidence: 79%
See 1 more Smart Citation